2010
DOI: 10.1002/etep.455
|View full text |Cite
|
Sign up to set email alerts
|

On-line fault detection method for induction machines based on signal convolution

Abstract: SUMMARYA new technique for induction motor fault detection and diagnosis is presented. This technique, which has been experimentally verified in stationary and non-stationary motor conditions, is based on the convolution of wavelet-based functions with motor stator currents. These functions are tuned to specific fault frequencies taking into account motor speed and load torque, thus considering variable operation conditions of the motor. Based on this technique an automatic system for fault diagnosis is also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…Researchers have published some works on broken rotor bar detection of IM using discrete wavelet transform (DWT) [19][20][21] and wavelet package decomposition (WPD) [8,22]. A few works has been reported on CWT for fault detection of IM [2,16,17]. However, in [2,16,17] the CWT was not adaptive in nature and authors analysed a single phase stator current signal which is not enough to detect the motor faults accurately.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Researchers have published some works on broken rotor bar detection of IM using discrete wavelet transform (DWT) [19][20][21] and wavelet package decomposition (WPD) [8,22]. A few works has been reported on CWT for fault detection of IM [2,16,17]. However, in [2,16,17] the CWT was not adaptive in nature and authors analysed a single phase stator current signal which is not enough to detect the motor faults accurately.…”
Section: Introductionmentioning
confidence: 97%
“…A few works has been reported on CWT for fault detection of IM [2,16,17]. However, in [2,16,17] the CWT was not adaptive in nature and authors analysed a single phase stator current signal which is not enough to detect the motor faults accurately.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wavelets have been the final solution to these concerns. The authors have discussed numerous works using wavelets for FD . They have given the research works based on the application of continuous wavelet transform, DWT, wavelet packet transform, and second‐generation wavelet transform for FD.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], the effects of the broken bar location have been studied, and it has been shown that the distribution of broken bars in different poles leads to the decrease in amplitude of side-band components in stator-current profiles. In [25], the convolution of wavelet-based functions of stator currents has been utilized for fault diagnosis in stationary and non-stationary motor conditions. It has been shown that ignoring the existence of inherent eccentricity due to manufacturing and installation procedure leads to error in precise broken bar fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%